2021
DOI: 10.1098/rsos.210774
|View full text |Cite
|
Sign up to set email alerts
|

The impact of moderate heating on human bones: an infrared and neutron spectroscopy study

Abstract: This study aims to analyse human bones exposed to low/medium temperatures (200–650°C) under experimentally controlled conditions, both oxidizing and reducing, using complementary optical and neutron vibrational spectroscopy techniques. Clear differences were observed between the aerobically and anaerobically heated bones. The organic constituents disappeared at lower temperatures for the former ( ca 300°C), while they lingered for higher temperatures in anaerobic environments ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 64 publications
5
27
0
Order By: Relevance
“…Between the fourth century BC and the first century AD, the cremation rite was prevalent in Ancient Roman civilization and inhumation was rare 23 . By comparing the results obtained here for the archaeological samples with published data previously gathered for modern human bones burned under controlled conditions (regarding temperature and oxygen availability) 14 16 , it is possible to estimate the temperatures to which the investigated archaeological samples were subject to. Table 1 summarizes the information gathered from the analysis of the experimental results from the previous section: (i) samples 2, 5, 7, 8, 9 and 10 found inside Aebutia’s sarcophagus, located in the central area of the skeleton, were subject to very mild heating ( ca.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Between the fourth century BC and the first century AD, the cremation rite was prevalent in Ancient Roman civilization and inhumation was rare 23 . By comparing the results obtained here for the archaeological samples with published data previously gathered for modern human bones burned under controlled conditions (regarding temperature and oxygen availability) 14 16 , it is possible to estimate the temperatures to which the investigated archaeological samples were subject to. Table 1 summarizes the information gathered from the analysis of the experimental results from the previous section: (i) samples 2, 5, 7, 8, 9 and 10 found inside Aebutia’s sarcophagus, located in the central area of the skeleton, were subject to very mild heating ( ca.…”
Section: Discussionmentioning
confidence: 67%
“…250 cm −1 . Previous work has shown that the lipid and protein components of bone disappear on heating to about 400 °C (under oxidizing conditions) 14 16 . From this evidence, one can conclude that rib1, tibia and carpal appear not to have been burned.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations